PENGARUH PERMAINAN BERBASIS KEARIFAN BUDAYA LOKAL TERHADAP KECEMASAN SISWA TAMAN KANAK-KANAK DI HUNIAN TETAP CANGKRINGAN SLEMAN - , OKKI DHONA LAKSMITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Mount Merapi eruption in 2010 at Sleman Regency, Yogyakarta had been create a traumatic response, especially for vulnerable population, one of them is preschool children (kindergaten schoolchild). Stressors that always come and continue time by time make them get higher anxiety. One of the way to reduce their anxiety is by giving them game based on local cultural wisdom. Objective:The study is aimed to identify influence of game based on local cultural wisdom to kindergaten schoolchildâs anxiety in dwelling Cangkringan, Sleman. Method: This was a quantitative study with quasi-experimental pretest and posttest control group design. The study had been done at Dwelling Cangkringan, Sleman, in February-April 2014. The total study sample consisted of 49 subjects for intervention group dan 49 subjects as well in control group. The study used SPAS (Spence Preschool Anxiety Scale) Parent Report and parametric t -test, Skala Pola Asuh Orang Tua, also Modul of Game Based on Local Cultural Wisdom. Result:There was a significant difference between intervention group and control group based on mean score of SPAS Parent Report (0,001 < 0,05). Before giving game based on local cultural wisdom, mean score of SPAS Parent Report in intervention group was 60,38Â±3,56 and in control group was 58,79Â±7,24. After giving game based on local cultural wisdom, mean score of SPAS Parent Report in intervention group was 43,18Â±3,19 and in control group was 57,57Â±7,20. Conclusion:Game based on local cultural wisdomhave a significant influence to reduce kindergaten schoolchildâs anxiety in Dwelling Cangkringan, Sleman.